Behavior Analysis and Politics (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
This paper aims at commenting the politic acting proposals by behavioral scientists as presented by B. F. Skinner’s articles gathered in the book Cumulative Records and confronted with J. G. Holland’s papers. The weakness of such proposals becomes clearer when one considers the incompatibility between behavioral science presuppositions and the conditions that actually determine the concrete institutionalized political power exercise. The importance of broad disclosure of behavioral control techniques, excluding both governmental institutions and opposing political party organizations as well.
Keywords: Behavior analysis; policy; power